The Influence of the Internet-Based Group Investigation Model on Students of Madrasah Ibtidaiyah Teacher Education - Nisrina Ajrina Nur Hidayah; Ali Mustadi; Sigit Prasetyo (AL-ISHLAH: Jurnal Pendidikan, 2023)
Students' creative thinking ability is one of the abilities that must be expanded in the science learning  process.  The  reality  of  a  pandemic  shows  that  being  able  to  integrate  with technology is an important point in the success of learning. This study aims to determine the effect  of  the  application  of  group investigation learning model assisted internet on students' interest. This is an research of one shot case study design which involved  PGMI  UIN Sunan Kalijaga students grades 6A and 6B taking science lectures. Descriptive analysis and inferential analysis were adopted in this research. Data was collected using questionnaire. The instrument  used  was  a  questionnaire  to  determine  students’  interest  response  during the teaching and learning process. The results showed that the application of the group investigation model had an effect on students’ interest in learning with the acquisition of a significance level value of 0,004  0.005 so that it had a positive effect.Keywords: group investigation, internet, interest in learning